A CEFR Informed Development of Digital Expository Text Resources for High School Students in Cirebon, Indonesia - Rifa Maryanti (JET ADI BUANA, 2023)
Indonesia's English Proficiency Index (EPI) has declined significantly over the past 11 years, according to Education First's annual report. The country's latest ranking is 81st out of 111 countries, indicating poor English performance. One of the contributing factors is the conventional pedagogy that focuses mainly on grammar, while the disregard of various forms of English literature, such as expository texts, impedes students' writing ability. Developing digital learning resources that provide new insights is crucial. So in this study investigates the key creative processes employed in the development of digital expository text resources for high school students in Indonesia and how these processes inform the characteristics of the product prototype. The research design is a qualitative approach, specifically a single-case study design, with the author being the only participant. Data collection methods included document analysis, and content analysis was used to analyze the data. The findings indicate that the key creative processes involved in the development of digital expository text resources include lesson plan analysis, text analysis, and CEFR analysis, among others. These processes informed the characteristics of the product prototype, including its visual design, interactive features, and pedagogical strategies. The study suggests that the development of digital expository text resources should be informed by the Common European Framework of Reference for Languages (CEFR) to align with the language proficiency levels of the target audience. This study provides valuable insights into the creative processes involved in the development of digital expository text resources and how these processes can inform the characteristics of the product prototype.